Friend or foe? : the invasive potential and aquacultural application of the sporophytic Falkenbergia stage of Asparagopsis armata in South Africa - Duncan, John A (Department of Biological Sciences, 2017)
The presence of the sporophytic 'Falkenbergia rufolanosa' phase of the invasive algal species Asparagopsis armata was first recorded in South Africa 57 years ago. The introduction of this highly invasive alga, of Australian/New Zealand origins, to Europe in the 1920's has since led to a number of recorded invasions by the gametophytic Asparagopsis phase in both the Mediterranean and Atlantic oceans. Recently however, a number of commercial uses for both phases of A. armata have been identified, which have given rise to industrial interest in the species as a candidate for commercial cultivation. Previous studies on European strains of F. rufolanosa and A. armata have identified a number of life history traits, which not only increase A. armata 's invasive ability, but also make it a useful species for commercial tank cultivation. However, different strains are known to have different environmental parameters which regulate their survival, growth and reproduction capabilities. This study investigated the growth of the South African strain of F. rufolanosa in culture, in response to different environmental variables, as well as the conditions necessary for tetrasporogenesis to occur, in order to assess its potential impacts, both as an invasive threat and as a species for commercial cultivation in South Africa.